Pengaruh Tingkat Pendidikan Orang Tua terhadap Prestasi Belajar Bahasa Indonesia pada Siswa SMP - Yulianti, Intan; Hamdani, Agus; Jamilah, Jamilah; Haryadi, Ardi Mulyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of parents' education level on student achievement in learning Indonesian. The method in this study uses a quantitative approach with a descriptive correlational research design. The research subjects were grade VIII students of junior high school consisting of 40 students. Instruments as data collection tools in the form of questionnaires and documentation. Data analysis techniques using simple and multiple regression tests. The results showed that between parents' educational level and students' Indonesian learning achievement there was a significant and positive influence with a large influence of 18.8%. As for the educational level of parents and learning motivation on students' Indonesian learning achievement, there is a significant and positive influence with a large influence of 30.1%. Based on the findings of this study, there is an influence of parents' educational level and learning motivation on learning achievement. Keywords: Indonesian, Learning Outcomes, Motivation, Education Level